Sustainability and the Insurance Market: Trends and Challenges - Bataller-Grau, Juan; Kawiński, Marcin; Marano, Pierpaolo (AIDA Europe Research Series on Insurance Law and Regulation, 2025)
This open access book focuses on the regulatory framework for the sustainability of the insurance market. It analyzes its potential impact on insurance undertakings governance and product design. The book is structured into three parts. It firstly explores the general framework on the sustainability for the insurance market, focusing on the regulation at the European Union level. Secondly, it examines sustainability and insurers' governance, including topics like sustainable investments and ESG factors. Finally, the book turns to sustainability and insurance products, addressing agricultural insurance systems and pensions. The book is aimed at academics, policymakers, and professionals in the insurance sector.